Assessment of potential land degradation and recommendations for management in the south subtropical region, Southwest China. (3rd March 2019) - Han, Wangya; Liu, Guohua; Su, Xukun; Wu, Xing; Chen, Li
Abstract: Land degradation is a global environmental problem that has received a great deal of attention. Moreover, the current methods used to evaluate land degradation concentrate mostly on point and management levels, while information at the regional scale is lacking. This study aimed to assess potential land degradation at a regional scale by adapting the Mediterranean desertification and land use approach for a subtropical region with a geographic information system (GIS), developing a degradation assessment model that recognizes environmentally sensitive areas and analyzing potential land degradation for natural and anthropogenic factors. The selected indicators included vegetation, soil, climate, and human pressure, and these four indicators contained 15 indices that were input by layers from GIS data. The results showed that 89.32% of the study area was affected by land degradation, with more than half of this region in the moderate risk class for land degradation. At the city scale, Nanning had the largest percentage of land in the critical class, followed by the cities of Chongzuo and Qinzhou. Climate and human pressure were the predominant indicators, with the highest mean scores of 1.46 and 1.45, respectively. This study offers significant information for decision makers evaluating potential land degradation. The goal of land management is to solve conflicts between humans and land, and management measures consider local conditions. The assessment model provides a basis for effective management measures and decision making for land degradation prevention. Developing this approach is significant in terms of extending degradation assessment to a larger scale.